Executive control in frontal lesion aphasia: Does verbal load matter?. (October 2019) - Kendrick, Luke T.; Robson, Holly; Meteyard, Lotte
Abstract: Executive control impairments in aphasia resulting from frontal lesions are expected, given that integrity of frontal regions is critical to executive control task performance. Yet the consistency of executive control impairments in aphasia is poorly understood. This is due to previous studies using only a brief set of measures or failing to account for the high language processing demands of many executive control tasks. This study investigated performance across a series of specific and broad executive control task, whilst comparing differences between low or high verbal task versions. Ten participants with aphasia secondary to left inferior frontal lesions and fifteen age matched controls completed a battery of verbal and low verbal executive control tasks tapping into the three core domains of inhibiting, switching, and updating of working memory. For both controls and participants with aphasia, there was no consistent influence of verbal load on either reaction time or accuracy performance. When compared to controls, participants with aphasia demonstrate a general slowing of responses across all reaction time tasks, and are less accurate on switching and updating tasks. These findings do suggest that language processing is not essential for executive control task performance, given that verbal load does not matter. Furthermore, tasks which involve holding multiple sources of information in mind, such as during switching or updating, are particularly vulnerable in aphasia. Highlights: We investigated performance on verbal and low-verbal executive control tasks in aphasia. . Verbal load of executive control tasks did not consistently influence performance in aphasia. . Participants with aphasia show a generalised cognitive slowing compared to controls. . Generalised cognitive slowing occurred for both baseline and executively demanding tasks. . Accuracy performance is impaired in aphasia for tasks of switching and updating of working memory, but not inhibition. .